Cover Picture: Local Deuteration Enables NMR Observation of Methyl Groups in Proteins from Eukaryotic and Cell‐Free Expression Systems (Angew. Chem. Int. Ed. 25/2021). Issue 25 (6th May 2021) - Dubey, Abhinav; Stoyanov, Nikolay; Viennet, Thibault; Chhabra, Sandeep; Elter, Shantha; Borggräfe, Jan; Viegas, Aldino; Nowak, Radosław P.; Burdzhiev, Nikola; Petrov, Ognyan; Fischer, Eric S.; Etzkorn, Manuel; et al.
Abstract : Methyl‐group NMR spectroscopy offers exceptional benefits for structural studies of complex biological systems. Yet, restrictive isotope labeling requirements have obstructed its use in emerging protein expression systems. In their Communication on page 13783, Manuel Etzkorn, Vladimir Gelev, Haribabu Arthanari, and co‐workers report a five‐step synthesis of stereoselectively methyl‐labeled leucine, which greatly facilitates applications in eukaryotic or cell‐free expression systems, providing desirable NMR sensors in so far inaccessible protein systems.